EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TAI DENGAN PENDEKATAN KONTEKSTUAL PADA POKOK BAHASAN BANGUN RUANG SISI DATAR DITINJAU DARI GAYA BELAJAR SISWA KELAS VIII SMP SE-KOTA KEDIRI - Nanndo Yannuansa; Mardiyana Mardiyana; Tri Atmojo Kusmayadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aim of the research was to determine the effect of learning models of TAI Type with contextual approach, learning models of TAI and direct learning model on mathematics achievement viewed from learning style. The type of the research was quasi experimental research using design factorial 3x3. The population was the students in grade VIII junior high school in a city of Kediri. The samples of the research consisted of 321 students; 107 students belonged to experiment class one, 103 students belonged to experiment class two, and 111 students belonged to control class. The data of the research were gathered through multiple choice test of learning achievement and questionnaire of learning style. Before giving the treatment, the population had to be in balanced condition. The balance test used one way analysis of variance with unequal cell frequencies. Test requirements included normality test used Lilliefors method and the homogeneity test used Bartlett method. The hypothesis test used two ways analysis of variance with unequal cell frequencies at the significance level of 0.05. The conclusions of the research were as follows. (1) Students who taught by cooperative learning model of TAI type with contextual approach have better mathematics learning achievement than TAI type and direct learning, the students who taught by cooperative learning model of TAI type have better mathematics learning achievement than direct learning. (2) Each of the learning styles of visual, auditory or kinesthetic does not have an influence on learning achievement. (3) In each learning style, the students who taught by the TAI with contextual approach have better mathematics learning achievement than TAI type and direct learning and the students who taught by cooperative learning model of TAI type have better mathematics learning achievement than direct learning. (4) In each learning model, the students with the visual, auditory, and kinesthetic learning styles have an equal learning achievement in Mathematics.Keywords: TAI learning models, contextual approaches, and learning style.